The initiative of the magistrate on the production of evidence in the Brazilian criminal proceedings from a foucaultian perspective - Alexandre Ribas de Paulo; Valine Castaldelli Silva; Gabriel Orsini Maziero (Revista Brasileira de Direito Processual Penal, 2020)
The present work consists of a study of the construction of the principle of real truth in the Brazilian penal process and its implications regarding the active legitimacy of the magistrate in the probative production, through the theoretical framework of social practices and the control of Foucaultian discourse. The research problem arose with the observation that after the promulgation of the Constitution of the Federative Republic of Brazil of 1988, the current Code of Criminal Procedure did not undergo significant reforms, and the rules that it lays down on the evidentiary powers of the judge in criminal prosecution persist. The method used is inductive. Finally, it is evident that, from a Foucaultian point of view, in reality the discourse of the search for a real truth is a strategy that is convenient to the institutions that retain criminal jurisdiction, since it represents interests that are unfair to those of the parties and to the purposes of the guarantees and fundamental rights enshrined in the Federal Constitution of 1988.